The Combined Algae Test for the Evaluation of Mixture Toxicity in Environmental Samples. (5th November 2020) - Glauch, Lisa; Escher, Beate I.
Abstract: The combined algae test is a 96‐well plate‐based algal toxicity assay with the green algae Raphidocelis subcapitata that combines inhibition of 24‐h population growth rate with inhibition of photosynthesis detected after 2 and 24 h with pulse‐amplitude modulated (PAM) fluorometry using a Maxi‐Imaging PAM. The combined algae test has been in use for more than a decade but has had limitations due to incompatibilities of the measurements of the 2 biological endpoints on the same microtiter plates. These limitations could be overcome by increasing growth rates and doubling times on black, clear‐bottom 96‐well plates by application of dichromatic red/blue light‐emitting diode illumination. Different robotic dosing approaches and additional data evaluation methods helped to further expand the applicability domain of the assay. The combined algae test differentiates between nonspecifically acting compounds and photosynthesis inhibitors, such as photosystem II (PSII) herbicides. The PSII herbicides acted immediately on photosynthesis and showed growth rate inhibition at higher concentrations. If growth was a similar or more sensitive endpoint than photosynthesis inhibition, this was an indication that the tested chemical acted nonspecifically or that a mixture or a water sample was dominated by chemicals other than PSII herbicides acting on algal growth. We fingerprinted the effects of 45 chemicals on photosynthesis inhibition and growth rate and related the effects of the single compounds to designed mixtures of these chemicals detected in water samples and to the effects directly measured in water samples. Most of the observed effects in the water samples could be explained by known photosystem II inhibitors such as triazines and phenylurea herbicides. The improved setup of the combined algae test gave results consistent with those of the previous method but has lower costs, higher throughput, and higher precision. Environ Toxicol Chem 2020;39:2496–2508. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : The combined algae test (CAT) allows cost‐efficient high‐throughput monitoring of chemicals and water samples for their algae toxicity with a diagnostic component to differentiate between the mixture effects of photosynthesis inhibitors and other chemicals.